Biotechnological production and application of antimicrobial biomolecules by Lactobacillus plantarum in milk whey - Sabo, Sabrina da Silva (2017)
Bacteriocins are antimicrobial peptides ribosomally synthesized by various bacteria. In particular, the bacteriocins produced by lactic acid bacteria have recently received great attention due to their wide applicability and also because they are produced by microorganisms safe for human consumption. There are numerous studies reporting bacteriocin production by different lactic acid bacteria, as well as its optimization by using alternative substrate. Some of these studies point to milk/cheese whey as a potential low-cost source for the cultivation of lactic acid bacteria and the production of biocomposites, such as bacteriocins. Several researches refer to the production of bacteriocins, mainly nisin. On the other hand, the production of bacteriocins by Lactobacillus plantarum strains still limited. In this context, the present work first studied the growth and production of bacteriocin by L. plantarum strain ST16Pa when cultivated in Man, Rogosa and Sharpe (MRS) broth with and without inulin supplementation incubated under shaken and stationary conditions. The results indicated that this strain has higher growth when cultured in aerobiosis; however, the highest bacteriocin activity is obtained in stationary condition. The stability and partitioning of bacteriocin from the fermented MRS broth of L. plantarum ST16Pa in the PEG/NaPA/electrolytes aqueous two-phase systems was also studied. After 1 h in temperatures from 50 °C to 80 °C and pH from 3.0 to 8.0, the produced bacteriocin remained stable. In addition, the proposed partition system has proved to be an economical alternative for the recovery and purification of this biomolecule. Motivated by the trend in use industrial by products aiming the production of high value-added biocomposites, we investigated the performance of milk/cheese whey as alternative substrate for L. plantarum ST16Pa growth and for the production of antimicrobial biomolecules by this strain. For this purpose, the study was divided in two steps, being the first developed using whey powder supplemented according to the Plackett & Burman experimental design, with 12 trials and 4 central points. Although the proposed design was not the ideal statistical tool to optimize the bacteriocin ST16Pa production, through it was possible to obtain a formulation, which resulted in greater inhibition zones when compared with previous date reported by other authors using the same strain cultured in cheese whey. Later, still using L. plantarum strain ST16Pa, we investigated the production of bacteriocin and lactate in fresh cheese whey previously hydrolyzed by Flavourzyme or Lactozym. The cultures were optimized by supplementing this medium with different concentrations of soybean flour, which were incubated under aerobic and microaerophilic/anaerobic conditions. The highest values of bacteriocin activity (7,367.23 AU/mL) and lactate yield (Ylactate/lactose = 1.39 g/g) were obtained under anaerobic conditions using 10 g/L of soybean flour to supplement cheese whey prehydrolyzed with Flavourzyme during 3 h. Finally, the cell-free supernatant resulted from this cultivation was applied on the surfaces of chicken breast fillets artificially contaminated with Enterococcus faecium 711, showing biopreservative efficiency during 7 days of storage under refrigeration.